2012
DOI: 10.1016/j.atmosenv.2011.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Long term monitoring of the chemical composition of precipitation and wet deposition fluxes over three Sahelian savannas

Abstract: International audienceThe purpose of this study is to analyze a long term database of the chemical composition of precipitation at three African dry savanna sites in the Sahel. The precipitation samples were collected during the monsoon season at Agoufou (15°20′N, 01°29′W, Mali) from 2004 to 2006, Banizoumbou (13°31′N, 02°38′E, Niger) from 1994 to 2009 and Katibougou (12°56′N, 07°32′ W, Mali) from 1997 to 2008. pH and major inorganic and organic ions in precipitation were analyzed by ionic chromatography. A ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
48
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 67 publications
11
48
3
Order By: Relevance
“…The average concentration of NO 2 in Abidjan (17.8 ppb) is more than 3 times higher than that measured in St John's in India (4.8 ppb) (Kumar et al, 2004). This concentration in Abidjan is comparable to those measured in Bamako (16.2 ppb) and Shenzhen (20.7 ppb) reported by Adon et al (2016) and Xia et al (2017).…”
Section: Traffic and Urban Sitessupporting
confidence: 46%
See 3 more Smart Citations
“…The average concentration of NO 2 in Abidjan (17.8 ppb) is more than 3 times higher than that measured in St John's in India (4.8 ppb) (Kumar et al, 2004). This concentration in Abidjan is comparable to those measured in Bamako (16.2 ppb) and Shenzhen (20.7 ppb) reported by Adon et al (2016) and Xia et al (2017).…”
Section: Traffic and Urban Sitessupporting
confidence: 46%
“…However, it remains lower than the concentrations obtained in Dakar (31.7 ppb) and Al Ain in the Middle East (31.5 ppb) and reported respectively by Adon et al (2016) and Salem et al (2009). The average concentration of NH 3 measured at the Abidjan traffic site (27.2 ppb) in this study is higher than those obtained in Dakar (21.1 ppb), Al Ain (17.1 ppb) and St John's (9.5 ppb), respectively reported by Adon et al (2016), Salem et al (2009) and Kumar et al (2004). Adon et al (2016) also reported a concentration of NH 3 in Bamako (46.7 ppb) 2 times higher than that obtained in Abidjan.…”
Section: Traffic and Urban Sitescontrasting
confidence: 43%
See 2 more Smart Citations
“…IDAF activity is based on high-quality measurements of atmospheric chemical data (gaseous, precipitation and aerosol chemical compositions) on the basis of multiyear monitoring (http://idaf.sedoo.fr). Within the framework of IDAF, several studies of precipitation chemical composition representative of great African ecosystems have been recently published (Galy- Lacaux and Modi, 1998;Galy-Lacaux et al, 2001Al-Ourabi and Lacaux, 2002;Lacaux et al, 1993Lacaux et al, , 2003Sigha et al, 2003;Yoboue et al, 2005;Mphepya et al, 2004;2006;Laouali et al, 2012).…”
Section: Introductionmentioning
confidence: 99%